'Akinnah intervention kit the guide to break free from 'akinnah' in the heart. - Abdul Kamil, Jamaludin
Akinnah means negative characteristics in the heart of man that has become a layer wrapping the heart and preventing the person from doing good and obeying the commands of Allah SWT.